Microbial safety of cellular therapeutics—lessons from over ten years' experience in microbial safety of platelet concentrates. (19th September 2018) - Störmer, Melanie; Wood, Erica M.; Gathof, Birgit
Abstract : Bacterial safety of cellular preparations, including blood products and cellular therapeutics, presents ongoing challenges for physicians, manufacturers and regulators. Although there have been many new approaches to enhance the microbial safety of cellular products during the last decade, established methods for microbiological control still need to be fully adapted to the special circumstances of cellular preparations. The experience from transfusion medicine regarding microbial safety of blood components has demonstrated the variety of problems and risk factors for the development of new strategies for microbial safety. Special attention has been given to the prevention and detection of bacterial contamination of platelet concentrates. But so far, none of the targeted strategies for rapid detection or pathogen reduction have become routinely implemented worldwide, in part at least because development and requirements of new technologies and their implementation into the routine setting are a whole different problem. But factors including the short shelf life and nontraditional lot sizes for cellular and gene therapy products are driving the need for rapid microbiological methods. In conclusion, lessons from the microbial safety of platelet concentrates enable us to understand that the detection or reduction in bacteria represents a more difficult challenge in comparison with viruses. Recent regulatory changes demonstrate that we are getting closer to the goal of a shift from the traditional view of sterility evaluation (identify and inactivate anything and everything) to a new thinking about microbiological control.